Potential surrogate quantitative immunomodulatory potency assay for monitoring human umbilical cord‐derived mesenchymal stem cells production. (2nd February 2021) - Teng, Sen‐Wen; Sung, Hsin‐Yu; Wen, Yu‐Chieh; Chen, Ssu‐Yu; Lovel, Ronald; Chang, Wen‐Ying; Wu, Tang Bo‐Chung; Hsuan, Yogi Cheng‐Yo; Lin, Willie
Abstract: Mesenchymal stem cells (MSCs) play an important role as immune modulator through interaction with several immune cells, including macrophages. In this study, the immunomodulatory potency of human umbilical cord‐derived mesenchymal stem cells (hUC‐MSCs) was demonstrated in the in vivo middle cerebral artery occlusion (MCAo)‐induced brain injury rat model and in vitro THP‐1‐derived macrophages model. At 24 h after induction of MCAo, hUC‐MSCs was administered via tail vein as a single dose. Remarkably, hUC‐MSCs could inhibit M1 polarization and promote M2 polarization of microglia in vivo after 14 days induction of MCAo. Compared with THP‐1‐derived macrophages which had been stimulated by lipopolysaccharide, the secretion of proinflammatory cytokines, tumor necrosis factor‐α (TNF‐α) and interferon‐γ inducible protein (IP‐10), were significantly reduced in the presence of hUC‐MSCs. Moreover, the secretion of anti‐inflammatory cytokine, interleukin‐10 (IL‐10), was significantly increased after cocultured with hUC‐MSCs. Prostaglandins E2 (PGE2), secreted by hUC‐MSCs, is one of the crucial immunomodulatory factors and could be inhibited in the presence of COX2 inhibitor, NS‐398. PGE2 inhibition suppressed hUC‐MSCs immunomodulatory capability, which was restored after addition of synthetic PGE2, establishing the minimum amount of PGE2 required for immunomodulation. In conclusion, our data suggested that PGE2 is a crucial potency marker involved in the therapeutic activity of hUC‐MSCs through macrophages immune response modulation and cytokines regulation. This study provides the model for the development of a surrogate quantitative potency assay of immunomodulation in stem cells production.